Fecal indicator bacteria diversity and decay in an estuarine mangrove ecosystem of the Xuan Thuy National Park, Vietnam. (2nd June 2022) - Nguyen, Thi Mai Huong; Le, Thi Phuong Quynh; Hoang, Vinh Van; Nhu, Da Le; Ha, Hoang Thi Thu
Abstract: Mangroves are complex and dynamic ecosystems that are highly dependent on diverse microbial activities. In this study, laboratory experiments and field studies for fecal indicator bacteria (FIB) decay rates are carried out for the first time in the Xuan Thuy Mangrove Forest Reserve of Vietnam. Results show that there are significant differences in bacterial diversity in the water of mangrove areas that have been deforested compared to those which have been planted. The highest mean total coliform (TC) and Escherichia coli (EC) values were found in the natural mangroves (3, 807±2, 922 and 964±1133 CFU 100 ml −1, respectively). The results indicated that the source of contamination and seasonal changes affect the abundance of fecal bacteria. These results were exceeding by far the safety guidelines for individual, non-commercial water supplies in most of the samples. In the planted mangrove sampling sites, the highest mean Fecal streptococci (FS) values of 1, 520±1, 652 CFU 100 ml −1 were found. Microbial die-off rates were calculated over 5 days, and observed to be systematically higher for TC than for EC. HIGHLIGHTS: The microbial dynamics in aquatic systems have been studied. Worked on a range of aquatic ecosystems, most recently on the Red River estuary. Experience in this area will be invaluable in understanding the ecological interactions between nutrients, phytoplankton, and bacteria. Experienced in using models to combine hydrology with biogeochemistry to understand carbon cycles and transport.